Place Marketing Strategy In Ecotourism:Theoretical And Practical Perspective. - Hassan, Fatimah; Sirat, Morshidi (Universiti Utara Malaysia, 2006)
In this globalization era,capability of place competitiveness will determine the continuity And sustainability of tourist location developments.